PERSEPSI MASYARAKAT TERHADAP PENGELOLAAN AIR LAHAN SAGU TADAH HUJAN DI SUB DAS SALU PAKU DAS RONGKONG - Yumna Yumna; Sugeng Prijono; Zaenal Kusuma; Soemarno Soemarno (Jurnal Penelitian Kehutanan BONITA, 2020)
The ecological feasibility of sago plants is not strong enough to determine sago as a commodity that can be developed in the upstream area. The research objective was to assess the community's perception of the strategy for water of sago land management in Salu Paku sub-watershed, the upper part of Rongkong watershed. The research begins with the socialization of the rainfed sago land water management strategy. The research consisted of two stages (before socialization and after socialization). The results showed that before the socialization, 100% of the community understood that sago land did not need water management, but after socialization, the community understood that sago could be developed in dryland conditions if there was water management. The community previously understood that it was not important to regulate the number of plants in one clump, after receiving additional information, generally, they wanted to regulate the number of sago trees by maintaining two tillers, one weaning plant, and two tillers during the weaning period. phase, and in the tree phase raise one tree plus one wean and two chicks. The public perception of water conservation measures before the socialization was doubtful 100%, after the socialization, the perception increased 95% (willing to make terraces and dead-end trenches), and 5% were still in doubt. Public perception about the addition of organic fertilizer to sago land before the socialization was doubtful 100%, after the socialization, 95% of the people agreed to add organic fertilizer, although 5% still had doubts